2010
DOI: 10.1080/01431161003727754
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the electromagnetic field variations in ELF frequency range registered by DEMETER over the Sichuan region prior to the 12 May 2008 earthquake

Abstract: International audienceAnalysis of the low frequency fluctuations of the magnetic and electric fields prior to a strong earthquake of magnitude 8.0 on 12 May 2008 in Sichuan Province is given. We analyse the disturbances of the ionospheric electromagnetic field prior to the earthquake starting 2 weeks before this event, but detailed analysis is given for 6 and 9 May, 6 and 3 days prior to the earthquake, when the observed effects were strongest. Special attention is given to the characteristics of the spectra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Many researchers have also performed investigations on seismo-ionospheric effects since the occurrence of the Wenchuan M S 8.0 EQ. These studies include at least ionospheric changes of ground-based ionosonde data [57][58][59][60][61][62][63][64], DEMETER satellite data [17,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], ground-based GPS satellite data [17,28,57,58,74,77,[79][80][81][82][83][84], radio occultation data from six microsatellites of FORMOSAT3/COSMIC (F3/C) data [81,84,85], and CHAMP (challenging minisatellite payload) satellite data [77].…”
Section: Spatial Ionospheric Anomaliesmentioning
confidence: 99%
“…Many researchers have also performed investigations on seismo-ionospheric effects since the occurrence of the Wenchuan M S 8.0 EQ. These studies include at least ionospheric changes of ground-based ionosonde data [57][58][59][60][61][62][63][64], DEMETER satellite data [17,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], ground-based GPS satellite data [17,28,57,58,74,77,[79][80][81][82][83][84], radio occultation data from six microsatellites of FORMOSAT3/COSMIC (F3/C) data [81,84,85], and CHAMP (challenging minisatellite payload) satellite data [77].…”
Section: Spatial Ionospheric Anomaliesmentioning
confidence: 99%
“…The observed effects were strongest on May 9 for ionospheric ELF electromagnetic field [71]. By analyzing the data of DEMETER ion density O + , Zhang et al [64] found that the value reaches to its minimum of 10,000/cm 3 on May 9, 3 days before the event (see Figure 3c).…”
Section: Electromagnetic Variations In the Ionospherementioning
confidence: 97%
“…On board satellites we observe this radiation at the same geomagnetic field lines where plasma density inhomogeneities are observed. Authors of [84] [85] have observed the intensive ELF radiation in the ionosphere during (1 -6) days before several EQs with great amplitude. It was shown that this radiation is correlated in time and space with the heating anomaly observed by NOAA-18 satellite at the eve of a huge EQ in 2008 in Sichuan.…”
Section: Electromagnetic Phenomenamentioning
confidence: 99%